Analysis of Regional Government Readiness in Facing Budget Efficiency: Financial Sustainability and Fiscal Resilience Perspectives - Ichsan, Hisyam; Amirullah, Sufyan; Novitasari, Eni; Yusuf Y.S, Muhammad (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the fiscal readiness of local governments in responding to national budget efficiency policies that demand an increase in fiscal independence. Many regions still exhibit high dependence on transfer funds and have narrow fiscal space due to the dominance of operational spending. Using an explanatory sequential mixed-methods approach, this study first maps the fiscal readiness of several local governments through an integrated framework of Financial Sustainability and Fiscal Resilience. Subsequently, in-depth case studies were conducted in high- and low-performing regions to explore the determining factors behind the performance differences. The quantitative results show a significant disparity among the regions. The qualitative findings reveal that fiscal independence in high-performing regions is driven by the strong political commitment of its leadership and strategic policy innovations. Conversely, the challenges in low-performing regions are rooted in the rigidity of large personnel expenditures and a limited economic base. This creates a paradox of "pseudo-efficiency" at the expense of capital spending for long-term development. This study recommends strategies for increasing local-source revenue based on political commitment and structural spending rationalization to increase local fiscal readiness.